Glimpse on the relationship between Feynman integral and integrable system - Abdul Aziz, Zainal (Department of Mathematics, Faculty of Science, 2004)
We briefly review recent attempts to relate the concept of Feynman integral and integrable systems. This constitutes an endeavour on our part in making the Feynman path integral into a mathematically meaningful entity.